Restructuring Industrial Sector and Economic Growth in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigated the effects of restructuring industrial sector on economic growth in Nigeria. The study sets to examine the effect of the manufacturing on economic growth in Nigeria, examine the impact of crude petroleum and natural gas on economic growth in Nigeria and investigate the effect of solid mineral mining on economic growth in Nigeria. The study adopted both primary and secondary source of data. The study employed Error Correction Model (ECM) and Auto Regressive Distributed Lag (ARDL) model for hypothesis testing. The findings of the study showed that Manufacturing (LnMAN) had a significant positive effect on economic growth in Nigeria. Crude petroleum and natural gas (LnCPN) had positive and significant impact on economic growth in Nigeria. Solid mineral mining (LnSMM) had an insignificant positive impact on economic growth in Nigeria. Therefore, the study concluded that restructuring industrial sector, if properly and adequately implemented, would certainly propel and facilitate economic growth, development and unity in Nigeria with positive multiplier effect on West African states and Africa as a whole. Hence, recommended that there is need for the government to develop stimulants for the manufacturing sector and manufacturers in form of tax incentives and credit facilities. A good road network to mining sites and a sufficient power supply will go a long way to boost the productivity of the sector. Government should encourage the production of more agricultural products that could be used as raw materials by manufacturing industries to achieve balanced growth between the agricultural and the manufacturing industries of the Nigerian economy.